IDEALISM AND ITS RELEVANCE IN THE PRESENT SYSTEM OF EDUCATION - Zahida Jan; Afshana Magrey (RADJA PUBLIKA, 2024)
Idealism, a philosophy emphasizing the mental and spiritual aspects of reality, has profoundly influenced educational theory and practice. Rooted in the works of Plato and other classical philosophers, idealism prioritizes intellectual, moral, and ethical development over mere acquisition of factual knowledge. In contemporary education, idealism remains relevant through its advocacy for holistic development, critical thinking, and the cultivation of self-realization. Modern educational practices, such as social-emotional learning, personalized learning, and the integration of the arts and humanities, reflect idealistic principles. However, idealism also faces criticisms for its abstract nature, potential elitism, and lack of emphasis on vocational training. Despite these challenges, idealism offers valuable insights into creating a balanced and comprehensive educational approach that nurtures well-rounded individuals capable of critical thinking and moral reasoning. Integrating idealistic principles with modern educational practices can address current educational challenges and foster a more enriching learning environment.